Visual Sensing and its Applications Integration of Laser Sensors to Industrial Robots - Gan, Zhongxue; Tang, Qing.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
(3z(BVisual Sensing and its Applications: Integration of Laser Sensors to Industrial Robots(3y (Bprovides comprehensive and up-to-date coverage of research and development on this robotic vision system. A laser-structured light is the main concern in discussions of visual sensing. Also addressed in this book are all components of the robotic vision system and an emphasis on how to increase the accuracy of the system using three levels of calibration. This includes calibration of the vision system (eye calibration), calibration of eye-to-hand configuration and calibration of robot kinematics (hand calibration). With the integration of the laser sensors to industrial robots numerous applications in the field of robotic welding, grinding, machining, inspection, and palletizing are illustrated based on practical engineering projects in order to demonstrate how the visual sensing is performed. The book will serve as a valuable resource for researchers and engineers in the areas of robotics and machine vision. Dr. Zhongxue Gan is a vice chairman and chief scientist of the ENN Group, China. He serves as a member of the National Energy Expert Consultation Committee of China and member of the National Coal Council of the USA. He is also a co-founder of Intersmart Robotic Systems Co. Ltd., China. He was a research fellow in flexible automation systems at ABB and a founding director of ABB Corporate Research Robot Laboratories, both in the USA and in China. Dr. Qing Tang is a co-founder and CEO of Intersmart Robotic Systems Co. Ltd., China and an adjunct professor in Physics at Sichuan University, China. He was a principle consulting engineer and project manager at the ABB Corporate Research Robot Laboratory in the USA.s
Introduction -- System of the visual servoing -- Formation of laser scanner -- Calibration of robot visual system -- Robot coordinate measuring machine (RCMM) -- Visual servoing applications and analysis -- Appendix.
Keywords: Engineering; Artificial intelligence; Computer vision; Engineering; Control, Robotics, Mechatronics; Image Processing and Computer Vision; Laser Technology, Photonics; Artificial Intelligence (incl. Robotics).